Integration of Customary Law and Islamic Law in Makassaarsche Chrestomathie Manuscript - Nur Fadhilah Mappaselleng; Abd Kadir Ahmad; Sitti Arafah; Abd. Karim; Zul Khaidir Kadir (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2026)
In the Makassar community, some of the customary legal norms are preserved in the Makassaarsche Chrestomathie, a manuscript compiled by B.F. Matthes in 1860. This article aims to explore how the Makassaarsche Chrestomathie manuscript addresses cases of homicide, adultery, and inheritance, and how the formulations and substantive contents of those customary legal norms are integrated with Islamic law. This study adopts a philological approach, employing interviews and document analysis as data collection methods. Content analysis and qualitative analysis are used to interpret the findings. The study reveals that: First, the manuscript outlines specific customary legal concepts, including puli (retaliatory killing) and sapu (paying compensation) related to homicide, sikatinroang (sleeping together) in the context of adultery, and tawa rua (men and women have an equal share) regarding inheritance. Second, there are both substantive and normative integration between customary law and Islamic law, although each retains its own distinctive features and conceptual uniqueness. Concepts puli and sapu indicate parallel Islamic qiá¹£Äá¹£ and diyah concepts. Sikatinroang has the same meaning as adultery or zinÄ in Islamic law. However, there are differences between customary law in inheritance distribution, which recognizes equal status between men and women, while Islam recognizes the concept of proportion.